Discussing Social Business Innovations: An Interview with Professor Muhammad Yunus - Michael Wirtz; Christine Volkmann; Muhammad Yunus (University of Wuppertal, Schumpeter School of Business and Economics, 2018)
Muhammad Yunus is one of the world's leading social entrepreneurs, having been awarded the Nobel Peace Prize for founding the Grameen Bank in Bangladesh. This microfinance institution is the largest one until today, counting eight million borrowers. We conducted research on Grameen Bank, related organisations and the concept of social business over the past years and asked Yunus questions which arose as a result of the research.
urn:nbn:de:hbz:468-20180606-103131-7
Keywords: 330; Social Business; Grameen Bank; Microfinance; Social Business Cities; Joint Ventures